Bright light exposure does not prevent the deterioration of alertness induced by sustained high cognitive load demands. (August 2017) - Borragán, Guillermo; Deliens, Gaétane; Peigneux, Philippe; Leproult, Rachel
Abstract: The present work investigated the effects of bright light exposure to prevent increased sleepiness and decreased alertness induced by a dual working memory task in which high cognitive demands (HCL) are adapted to the individual's maximal capacity. In a randomized cross-over study, twenty participants were exposed to two sessions that included 20 min of light exposure (dim light or bright light). Subjective sleepiness (Karolinska Sleepiness Scale) and objective alertness (Psychomotor Vigilance Task) were assessed before and after light exposure and before and after performing with the high cognitive demands task. Bright light exposure did not prevent decreased alertness and increased sleepiness prompted by the task. These results suggest that bright light administered prior to a cognitively demanding task is not beneficial to prevent impairments ensuing from high cognitive demands. Highlights: Alertness decreases and self-reported feelings of sleepiness increased following sustained high cognitive demands. Bright light exposure did not counteract subsequent decrease in vigilance and increase in sleepiness. Beneficial effects of light exposure may not be effective when bright light is administrated before a high cognitive load condition.